2007
DOI: 10.1007/s00198-007-0495-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of trabecular bone structure comparing magnetic resonance imaging at 3 Tesla with high-resolution peripheral quantitative computed tomography ex vivo and in vivo

Abstract: Both imaging modalities were found to perform equally well regarding trabecular bone measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 27 publications
5
77
2
1
Order By: Relevance
“…First, partial volume effects, produced when imaging trabeculae that are smaller than the spatial resolution, may confound and overestimate measures of bone microarchitecture such as BVTV and Tb.Th (9,20). However, studies have demonstrated that "apparent" histomorphometric measures derived from MRI correlate well with measures derived through the use of higher-resolution modalities, such as micro-computed tomography, wherein partial volume effects are mitigated (21). Second, the 195 m in-plane resolution limited our ability to resolve cortical bone, which is more porous in individuals with type 2 DM (47).…”
Section: Pritchard Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…First, partial volume effects, produced when imaging trabeculae that are smaller than the spatial resolution, may confound and overestimate measures of bone microarchitecture such as BVTV and Tb.Th (9,20). However, studies have demonstrated that "apparent" histomorphometric measures derived from MRI correlate well with measures derived through the use of higher-resolution modalities, such as micro-computed tomography, wherein partial volume effects are mitigated (21). Second, the 195 m in-plane resolution limited our ability to resolve cortical bone, which is more porous in individuals with type 2 DM (47).…”
Section: Pritchard Et Almentioning
confidence: 99%
“…It has been argued, however, that the resolution of MRIs limits the accurate assessment of such 2-D variables because the images are acquired at the current limits of clinical spatial resolution and can be confounded by partial volume effects (20). However, MRI-based assessment of microarchitecture has proven to be promising because these "apparent" 2-D measures derived using MRI correlate well with measures derived by direct histomorphometry and higher resolution imaging (9,14,21).…”
Section: Introductionmentioning
confidence: 99%
“…High correlation has been found also for trabecular number and spacing by comparing 3.0 T MR and high resolution pQCT. Histomorphometry and other different structural analysis techniques applied to both modalities provide different absolute values but high correlation (r > 0.8) for all bone structure parameters [34] . Micro-MR units with special high-field-strength (7 T, 11 T or higher) are used in experimental settings to obtain highresolution MR images of small animals in vivo or bone specimens in vitro.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…MRderived structural dimensions are similar, but not identical, to histological or microcomputed tomography (CT) dimensions and a twodimensional rather than threedimensional approach is applied [34,35] . A magnetic susceptibility difference of about 3 ppm existing between bone and marrow leads to signal dampening at the bonemarrow interface and, as a result, an artificial overestimation of trabecular dimension occurs.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation